VERDADE E REALIDADE NA HISTORIOGRAFIA ANTIGA - Cairus, Henrique (Organon, 2010)
This paper intends to propose a review on the concepts surrounding theanalysis of the historiographical production during Antiquity, such as: truth, reality,data, testimony, evidence, facts, res ficta and res gesta. It was intended to focus on theeldest reception perspective in these works.